Population pharmacokinetic modelling to address the gaps in knowledge of commonly used HIV and TB drugs in children - Tikiso, Tjokosela (Department of Medicine, 2022)
The epidemiology of HIV and TB are overlapping, particularly in sub-Saharan Africa, and TB infection remains common in HIV-positive children. The combined administration of anti-tubercular and antiretroviral therapies(ART) may lead to drug-drug interactions potentially needing to be addressed with the adjustment of doses. This thesis assessed the pharmacokinetics of abacavir and ethambutol and evaluated the influence of covariates such as age and concomitant medication on the PK parameters across different studies using nonlinear mixed-effects modelling. The models developed were used to estimate area under the concentration-time curve (AUC) and maximum concentrations (Cmax) achieved with the currently-recommended weight-adjusted doses. A web-based paediatric dosing tool, which is meant to be used as a first step in the design of clinical trials for paediatric dosing was also developed. The model describing the pharmacokinetics of abacavir found: a) abacavir exposure to be 18.4% larger (CI:7.50-32.2) after the first dose of ART compared to abacavir co-treated with standard lopinavir/ritonavir for over 7 days, possibly indicating that clearance is induced with time on ART, b) malnourished HIV infected children had much higher exposures but this effect waned with a half-life of 12.2 (CI: 9.87-16.8) days as children stayed on nutritional rehabilitation and recovered, c). during co-administration of rifampicin-containing antituberculosis treatment and super-boosted lopinavir/ritonavir, abacavir exposure was decreased by 29.4% (CI: 24.3-35.8), d) children receiving efavirenz had 12.1% (CI: 2.57-20.1) increased abacavir clearance compared to standard lopinavir/ritonavir. The effects did not result in abacavir exposures lower or higher than those reported in adults and are not likely to be clinically important. The ethambutol model found lower concentrations than those reported in adults. The predicted ethambutol median (IQR) Cmax was 1.66 (1.21-2.15) mg/L for children on ethambutol with or without ART (excluding super-boosted lopinavir/ritonavir) and 0.882 (0.669-1.28) mg/L for children on ethambutol with super-boosted lopinavir/ritonavir, these are below the lower limit of the recommended Cmax range of 2 mg/L. During co-administration with super-boosted lopinavir, ethambutol exposure was decreased by 32% (CI: 23.8-38.9), likely due to drug-drug interaction involving absorption, metabolism or elimination. Bioavailability was decreased in children who were administered ethambutol in a crushed form, with an estimate decrease of 30.8% at birth, and an increase of 9.6% for each year of age up to 3.2 years where bioavailability was now similar to children taking EMB full tablet. The developed paediatric dosing tool contains two major sections. a) the ‘generic module’ which uses allometric scaling -based predictions to explore the expected AUC for a generic drug, b) the ‘drug-specific module’ which can simulate entire pharmacokinetic profiles (concentration over time after dose) by using a drug-specific population pharmacokinetic model. In summary, under the current weight-adjusted doses, abacavir exposure remained within the adult recommended levels. Ethambutol dose adjustment would be required in order to achieve adult exposures. A web-based paediatric dosing tool that uses allometric scaling -based predictions as well as drug specific predictions based on published pharmacokinetic models was successfully developed.